Negotiation - Yip, Dorothy Woon Yee (2017)
Negotiation is a photographic installation seeking to liberate the body. It is an attempt to reconcile perspectives as well as a question as to what true liberation is. By abstracting the body, I implore the viewer to consider an alternative perspective on it, removing all connotations and associations that one would usually have.